Laparoscopic bowel resection combined with infliximab treatment (LaRIC) versus infliximab for terminal ileitis in Crohn's disease: a randomised, controlled, open-label trial. Issue 11 (16th November 2020) - Hao, Xiuxiu; Feng, Tienan; Yang, Yang; Shi, Yuan; Jing, Ran; Liu, Sailiang; Luo, Yang; Qiao, Yuqi; Zhong, Ming; Yu, Minhao
Abstract : Introduction: Crohn's disease is a chronic inflammatory disease of the gastrointestinal tract with an increasing incidence and prevalence worldwide. The early use of anti-tumour necrosis factor agents, such as infliximab, in patients with an aggressive form of Crohn's disease has become part of routine practice. However, infliximab has limitations, and early surgery might benefit patients more. The objective of this study was to compare laparoscopic bowel resection with infliximab treatment in patients with moderately or severely active Crohn's disease with respect to endoscopic remission. The laparoscopic bowel resection combined with infliximab treatment trial is the first randomised controlled trial to demonstrate if early surgery can improve the outcome of patients with Crohn's disease with limited non-stricturing disease treated with infliximab. Methods and analysis: This is a randomised, open-label, controlled trial at Renji Hospital. In this study, a total of 106 adult patients aged 18–80 years with moderately or severely active and steroid-dependent or steroid-resistant Crohn's disease of the distal ileum will be randomly assigned in a 1:1 ratio to the control and surgery groups. The primary outcome is 12-month endoscopic remission measured by the Simple Endoscopic Score for Crohn's Disease in the control group and the Rutgeerts score in the surgery group. The secondary outcomes are clinical remission, surgery rate, quality of life, Crohn's disease-related medical costs and Crohn's disease-related morbidity. The patients will be followed up every 6 months after randomisation through intestinal magnetic resonance enterography and colonoscopy for either 3 years or until clinical remission. Ethics and dissemination: All participants will provide informed consent. The protocol has been approved by the Medical Ethical Committee of the Academic Medical Center in Shanghai (No KY2019-180). Results will be disseminated through peer-reviewed journals and scientific conference presentations. Trial registration number: ChiCTR2000029323.